COMPARATIVE ANALYSIS OF ONE’S OWN COUNTRY IMAGES IN RUSSIAN REGIONS - Elena B. Shestopal; Natalia V. Smulkina; Irina V. Morozikova (Сравнительная политика, 2019)
The article presents the results of a study of Russia’s the perception by its citizens, implemented at the Chair of Sociology and Psychology of Politics, Faculty of Political Science, Moscow State University. The research was devoted to the Russia’s in the minds of residents of different regions. The research technique of the study included methods of semi-structured interviews and projective tests. To interpret the data, the authors used both qualitative and quantitative methods, in particular, coding and scaling of answers to open-ended questions and statistical analysis. The article presents the results of a comparative analysis of images of their country among residents of 11 regions of Russia. This analysis is also complemented by 3 case-studies from Moscow, Smolensk and the Tyva Republic. The image of the country in the minds of Russians was tackled on two levels of perception: rational and unconscious. Authors focuse of the most important structural elements of the image: territory, people, authorities, leaders and the geopolitical role of the country. The study made it possible to interpret the peculiarities of Russia's perception in regions by different federal status. The conclusions highlight the problem of the formation in Russia of nation-state identity and the construction of consistent images of the past and the future, in which images of the country should find their place. The basis for the formation of a congruent image of the country is seen, above all, in moral determinants, which have not only high, but priority importance in political perception of their country.